Pengembangan Model Aplikasi Manajemen Insentif dan Data Luaran Penelitian pada Perguruan Tinggi Swasta Menggunakan Web Development Life Cycle - Wachyu Hari Haji (Jurnal Sistem Informasi dan E-Bisnis, 2024)
The application of research management in universities is essential not only within universities but also outside academia to support the improvement of scientific activities. Various studies emphasize the importance of research management systems in universities by developing applications for publications, data repositories, and continuous research processes. The purpose of this study is to propose an application model of incentive management and research output data at private universities in a structured manner using the Web Development Life Cycle (WDLC). Based on the results of the study, WDLC can be used as a stage to support structuring on unstructured problems and keep users engaged throughout the development lifecycle. This proposed application model consists of an output data input process, user data, reviewer data and review process data.